Biofunctionalization of β-cyclodextrin nanosponges using cholesterol. (15th June 2018) - Singh, Parbeen; Ren, Xiaohong; Guo, Tao; Wu, Li; Shakya, Shailendra; He, Yaping; Wang, Caifen; Maharjan, Abi; Singh, Vikramjeet; Zhang, Jiwen
Graphical abstract: Highlights: Surface of β-CD-NSP bioactivated with cholesterol through one step chemical reaction. Change hydrophilic surface to hydrophobic surface of β-CD-NSP. A HPLC method developed for quantification of CHS in β-CD-NSP by using ELSD detector. Enhanced the cellular uptake of Doxorubicin and biofriendly in nature. Abstract: Cyclodextrins nanosponges (CD-NSPs) are highly microporous crosslinked polymers with potential applications in the delivery of small and macro-molecular therapeutic agents. Despite the potent host-guest inclusion property, their inherent lack of cellular binding ability has limited applications in drug delivery. Herein, we functionalized the surface of β-cyclodextrin nanosponge (β-CD-NSP) with cholesterol, which is endogenous physiological molecules, widely distributed in all cells, and responsible for cell interactions and protein binding. The surface grafting of synthesized β-CD-NSP was confirmed with spectroscopic, microscopic, thermogravimetric, and chromatographic techniques. Moreover, β-CD-NSP was found to be safe in cytotoxicity assay. Doxorubicin (Dox) was selected as a model drug for drug adsorption study of cholesterol hydrogen succinate (CHS) grafted β-CD-NSP. The cellular uptake of NSP was found to be enhanced after CHS modification confirmed by confocal laser scanning microscopy (CLSM). Thus, proposed CHS modified β-CD-NSP system could be used as a site-specific drug delivery carrier.